Berberine suppresses hepatocellular carcinoma progression by blocking IL-4-JAK1-STAT6-mediated M2 polarization of macrophage - Wang, Peng; Zhong, Yuwen; Li, Mengkai; Liang, Qing; Jiang, Weiyi; Zhuang, Mengqi; Ge, Xuecheng; Li, Huixing; Zhang, Yaoshuai; Qiao, Yu; Jiang, Jiayao; Hu, Heping; et al. (Frontiers in Pharmacology, 2026)
Berberine (BBR), an isoquinoline alkaloid extracted from Coptis chinensis, is clinically used to treat chronic colitis, diabetes, and other diseases. Although BBR has antitumor effects, it is unclear whether it can inhibit hepatocellular carcinoma (HCC) by modulating the tumor inflammatory microenvironment. In this study, we demonstrated that BBR inhibits HCC development in mice by suppressing the M2 polarization of macrophages. Using an H22 tumor-bearing xenograft mouse model, we found that BBR significantly inhibited H22 tumor growth. Analysis of scRNA-seq results revealed reduced M2 macrophage infiltration and polarization in BBR-treated HCC tissues. Pharmacodynamic studies showed that BBR treatment markedly increased CD8+ T cell infiltration and attenuated M2 polarization. In vitro, BBR suppressed IL-4 or tumor cell supernatant-induced M2 polarization, as evidenced by decreased expression of M2 polarization marker genes (Arg1, Retnla, etc.) and reduced JAK1/STAT6 phosphorylation levels. Molecular docking and protein stability assays revealed that BBR directly binds to JAK1’s FERM domain, stabilizing it. Combination therapy with BBR and anti-PD-L1 antibody synergistically inhibited H22 tumor growth. These findings suggest that BBR can reduce the M2 polarization of tumor-associated macrophages (TAMs) by targeting the IL-4-JAK1-STAT6 axis, and combining with anti-PD-L1 antibody may represent a promising therapeutic strategy to enhance BBR’s antitumor efficacy.